Cardiac mortality benefit of direct admission to percutaneous coronary intervention–capable hospital in acute myocardial infarction: Community registry–based study. Issue 10 (12th March 2021) - Kang, Min Gyu; Kang, Yoomee; Kim, Kyehwan; Park, Hyun Woong; Koh, Jin-Sin; Park, Jeong Rang; Hwang, Seok-Jae; Ahn, Jong-Hwa; Park, Yongwhi; Jeong, Young-Hoon; Kwak, Choong Hwan; Hwang, Jin-Yong
Abstract : Abstract: Appropriate risk stratification and timely revascularization of acute myocardial infarction (AMI) are available in percutaneous coronary intervention (PCI) – capable hospitals (PCHs). This study evaluated whether direct admission vs inter-hospital transfer influences cardiac mortality in patients with AMI. This study was conducted in the PCH where the patients were able to arrive within an hour. The inclusion criteria were AMI with a symptom onset time within 24 hours and having undergone PCI within 24 hours after admission. The cumulative incidence of cardiac death after percutaneous coronary intervention was evaluated in the direct admission versus inter-hospital transfer groups. Among the 3178 patients, 2165 (68.1%) were admitted via inter-hospital transfer. Patients with ST-segment elevation myocardial infarction (STEMI) in the direct admission group had a reduced symptom onset-to-balloon time (121 minutes, P < .001). With a median period of 28.4 (interquartile range, 12.0–45.6) months, the cumulative incidence of 2-year cardiac death was lower in the direct admission group (NSTEMI, 9.0% vs 11.0%, P = .136; STEMI, 9.7% vs 13.7%, P = .040; AMI, 9.3% vs 12.3%, P = .014, respectively). After the adjustment for clinical variables, inter-hospital transfer was the determinant of cardiac death (hazard ratio, 1.59; 95% confidence interval, 1.08–2.33; P = .016). Direct PCH admission should be recommended for patients with suspected AMI and could be a target for reducing cardiac mortality.